Étude de la fidélité de l’implantation d’un programme de réadaptation au travail auprès de travailleurs de la construction ayant une dorsolombalgie - Marie-José Durand; Diane Berthelette; Patrick Loisel; Daniel Imbeau (Perspectives Interdisciplinaires sur le Travail et la Santé)
Few program evaluation studies on occupational health and safety have as yet been conducted. The goal of this study was to increase our understanding of the various mechanisms of a work rehabilitation program by: (1) describing the quantity and quality of the activities taking place and the resources used; and (2) estimating how faithful the implemented program was to the originally planned model. A descriptive study of the fidelity of the program’s implementation was conducted using different units of analysis. The results highlighted variations in the program’s implementation and some differences between what was planned and what was implemented.